2012
DOI: 10.4018/jthi.2012100106
|View full text |Cite
|
Sign up to set email alerts
|

Online Trust and Health Information Websites

Abstract: This study develops and tests a model of online trust of a health care website. The model showed a statistically strong fit to the data (N=176). Trust was significantly explained by perceptions of credibility, ease of use, and risk. Perceived ease of use was a direct predictor of trust and an indirect predictor through credibility. Credibility was both a direct predictor of trust and an indirect predictor through risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 58 publications
1
44
0
2
Order By: Relevance
“…For example, Freeman and Spyridakis [37] in their study on the measure of Web-based credibility, described credibility itself as being defined by two main components: trustworthiness and expertise, but Corritore et al [11] found that credibility was one of the direct predictors of trust. The objectivity of the information is also equally important and usually defined by authors in terms of how impartial and unbiased the source is.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Freeman and Spyridakis [37] in their study on the measure of Web-based credibility, described credibility itself as being defined by two main components: trustworthiness and expertise, but Corritore et al [11] found that credibility was one of the direct predictors of trust. The objectivity of the information is also equally important and usually defined by authors in terms of how impartial and unbiased the source is.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Corritore et al. () showed that trust in health websites was significantly explained by students' perceptions of website credibility, ease of use, and risk, while Robins, Holmes, and Stansbury () demonstrated that visual design judgments correlate with credibility ratings of health information websites. Recently, Rowley, Johnson, and Sbaffi () developed a scale that shows that authority, style, content, usefulness, brand, ease of use, recommendation, credibility, and verification are all influencers of trust formation in online health information seeking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, health information seekers encounter a plethora of different web‐based and other sources of health information, from a variety of organizations and individuals, and of varying quality, accuracy, and reliability (Eysenbach & Kohler, ; Fergie, Hunt, & Hilton, ; Kitchens, Harle, & Li, ). This presents individuals with significant challenges in evaluating and selecting the sources to use, and more specifically in assessing the credibility and trustworthiness of those sources (Corritore, Wiedenbeck, Kracher, & Marble, ; Gray, Kelin, Noyce, Sesselberg, & Cantrill, ; Metzger & Flanagin, ). Furthermore, consumers may lack the motivation or literacy skills to evaluate the information quality of health web pages, and digital inequalities may influence the extent of individual's health information repertoires (Chen, Lee, Straubhaar, & Spence, ; Stvilia, Mon, & Yi, ).…”
Section: Introductionmentioning
confidence: 99%
“…15,35]. The relevance, quality, usefulness and accuracy of information are known determinants that the information content is trustworthy [36]. The presentation, ease of use and clarity of information are linked to perceptions of 'professionalism' that, again, underpin judgements of trust [37]; [4]; [38] and, finally, the beliefs about objectivity and impartiality of the source also ensure trust [15], [16].…”
Section: Discussionmentioning
confidence: 99%